XEN® Implant and Trabeculectomy Medium-Term Quality of Life Assessment and Comparison of Results - Basílio, AL (2018)
AIM: To evaluate and compare the quality of life of patients submitted to XEN® implant or trabeculectomy and the relationship with potentially involved variables. METHODS: A cross-sectional study of patients with advanced open-angle glaucoma who underwent implantation of XEN® (group 1) and trabeculectomy (group 2) between October 2015 and February 2017. The studied variables were: age, gender, follow-up time, need of topical anti-hypertensive therapy, visual acuity and intraocular pressure (IOP). The quantification of the quality of life was attained through the Glaucoma Symptom Scale (GSS) questionnaire. RESULTS: Totally 34 eyes (34 patients) were included, 17 in each group. The mean GSS scores for group 1 were 42.6±6.8 (median, 47; p25, 36.5; p75, 48.5) and for group 2 it was 41.6±7.0 (median, 43; p25, 36.5; p75, 47.0; P=0.34). There was a strong negative correlation between the need for topical anti-hypertensive drugs and the GSS result in both groups (r=-0.88, P<0.01, r=-0.59, P=0.01, respectively) and a moderate negative correlation with IOP in group 1 (r=-0.50, P=0.03). CONCLUSION: The analysis demonstrates the non-inferiority of medium-term quality of life of one group in relation to the other (XEN® implant and trabeculectomy). The number of topical anti-hypertensive drugs and IOP negatively influenced the quality of life.